2021
DOI: 10.1177/10608265211032097
|View full text |Cite
|
Sign up to set email alerts
|

Transitions Into and Out of Work: Stay-at-Home Fathers’ Thoughts and Feelings: A Brief Report

Abstract: This qualitative study explored how stay-at-home fathers (SAHFs) think and feel about transitioning back into paid employment. Findings from a thematic analysis on interviews with 21 SAHFs in the United Kingdom revealed that many of the SAHFs expected to return to work. However, most of the fathers suggested that this would be part-time, or self-employment, which would allow them to remain highly involved in caregiving, representing their commitment to moving away from the traditional gender roles that are lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…By doing so, these fathers offer new perspectives on practices of masculinity and fatherhood and develop new masculine identities. Similar processes have been found among stay-at-home fathers [ 72 , 73 ], who represent another distinctive group of nonhegemonic fathers [ 64 ]. Thus, the insights gained here go beyond the specific case of single gay fathers.…”
Section: Discussionsupporting
confidence: 69%
“…By doing so, these fathers offer new perspectives on practices of masculinity and fatherhood and develop new masculine identities. Similar processes have been found among stay-at-home fathers [ 72 , 73 ], who represent another distinctive group of nonhegemonic fathers [ 64 ]. Thus, the insights gained here go beyond the specific case of single gay fathers.…”
Section: Discussionsupporting
confidence: 69%
“…In our study, fathers reported that each parent performed different roles and that, despite shifting societal norms surrounding parenting, there remained an implicit assumption that mothers would provide the majority of day-to-day care for their child with cancer (Jones et al, 2021;Reis et al, 2017). Goldscheider et al (2015) contend that while women have an increased role in the workforce, they are still expected to carry a larger burden of care for children and that this impedes a true "gender revolution."…”
Section: Discussionmentioning
confidence: 99%
“…In the previous decade, there has been a societal shift in fathers’ roles in parenting in the general population, with a growing expectation that fathers play a more active role in caregiving (Banchefsky & Park, 2016; Borgkvist et al, 2020; Jones et al, 2021; Reis et al, 2017). However, the extent to which gendered parental roles have shifted may be culturally specific.…”
mentioning
confidence: 99%
“…This finding highlights that societal understandings of fatherhood may be more varied than understandings of motherhood, and this should be understood in the context of intensive motherhood ideologies (Faircloth, 2014 ). Contemporary fatherhood research has demonstrated that cis fathers experience tension between caring masculinities and traditional masculinities (Hunter et al, 2017 ; Jones et al, 2021 ), and findings from this study demonstrate that TNB parents, whether or not they identify as fathers, are at the forefront of renegotiating fatherhood in novel and diverse ways. Participants’ experiences therefore highlight the differences and relationships between parental identifications at an individual/interpersonal level, and the societal level meanings of such terms.…”
Section: Discussionmentioning
confidence: 52%
“…Such disparities are also reflected in the relationship between policy and practice – although the UK government does now allow shared parental leave, uptake remains very low (Birkett & Forbes, 2019 ), suggesting that changing policy has not yet led to change in practice. Indeed, research with primary caregiver fathers has found that they negotiate with traditional forms of masculinity, rather than overcoming them entirely: retaining, for example, an emphasis on contributing financially to the family (Jones et al, 2021 ). There is thus a tension between hegemonic and caring masculinities that is evidenced in both research and practice.…”
Section: Introductionmentioning
confidence: 99%